Study on nylon strip-soil interaction / Iqraz Nabi Khan and Swami Saran - Nabi Khan, Iqraz; Saran, Swami (Universiti Teknologi MARA, Pulau Pinang, 2005)
An attempt has been made to explore the possibility of use of nylon strips (niwar) for reinforcing soil by conducting a study on frictional characteristics of nylon strips and soil using pull-out and sliding shear tests. Effect of over burden pressure and density of soil on coefficient of friction between soil and nylon strip has been studied. The friction coefficient decreases with increase in overburden pressure and decrease in density.